HDX-MS reveals dysregulated checkpoints that compromise discrimination against self RNA during RIG-I mediated autoimmunity - Jie Zheng (Nature Portfolio, 2018)
RIG-I is a critical receptor in the induction of innate immune responses, but mutations in RIG-I can be associated with hyperactive signalling and autoimmune disease. Here Zheng et al. apply HDX-MS approaches to reveal dysregulated checkpoints that result in recognition of self-derived RNA during RIG-I mediated autoimmunity.